Gastrointestinal Hemorrhage from Portal Vein Pseudoaneurysm after Pancreaticojejunostomy in Chronic Calcific Pancreatitis: A Stent Graft Rescue - Kumar, Saurabh; Batra, Apoorva; Javed, Amit; Yanger, Narola; Ahuja, Ankit (Journal of Clinical Interventional Radiology ISVIR, 2025)
Pseudoaneurysms of the portal vein are rare vascular abnormalities resulting from causes, including trauma, pancreatitis, or pancreaticobiliary surgery. They can be asymptomatic, but can present with significant gastrointestinal bleed, despite low pressure gradient in venous systems. We describe a rare case of symptomatic portal vein pseudoaneurysm following pancreaticojejunostomy surgery, presenting with massive gastrointestinal hemorrhage, which was subsequently managed with a percutaneous transhepatic portal stent graft.
Keywords: pseudoaneurysm; chronic pancreatitis; pancreaticojejunostomy